Investigating the expression of soluble pd-l1 (spd-l1) of breast cancer patients using elisa in Hospital USM, Kelantan - Anwar, Nur Amira Khairil (2024)
There are limited data on soluble PD-L1 (sPD-L1) in breast cancer, particularly those involving Asian (Malaysian) women, despite the fact that increased serum and plasma levels of sPD-L1 have been observed in numerous malignancies. This study was designed to achieve three aims: (1) to recruit breast cancer patients at Hospital University Sains Malaysia (HUSM) and examine the overall survival (OS) with clinicopathological properties and patient baseline, (2) to develop a sensitive and specific enzyme-linked immunosorbent assay (ELISA) using commercialised PD-L1 monoclonal antibody clones (mAb), 22C3 (Dako) and 28-8 (Abcam) for sPD-L1 detection and measurement in human peripheral blood , and finally (3) measure sPD-L1 level using the developed ELISA followed by analyse its correlation and OS with clinical characteristics in breast cancer patients at HUSM. Blood specimens were obtained from three cohorts of breast cancer patient: 92 malignant, 16 benign and 23 healthy controls. Our study demonstrated that triple negative breast cancer (TNBC) molecular subtype have lower OS than the non-TNBC (53 months (SD 5.4 months) vs 272.7 months (SD 7.5 months), p= 0.029, log-rank test). Similarly, patients presenting with advanced tumour staging at diagnosis has poorer prognostic (p<0.001, log-rank test). Using 22C3 as the capture antibody, and clone 28-8 as the detection antibody, a sandwich ELISA was successfully developed with the limit of detection (LoD) of 0.063 ng/mL in human serum and 0.078 ng/mL in human plasma. The median serum sPD-L1 concentration of malignant and benign patient cohorts was significantly elevated compared to the healthy cohorts (12.50 ng/mL vs 13.97 ng/mL vs 8.75 ng/mL, p<0.05). Optimal cut-off value of serum sPD-L1 for this study was 8.84 ng/mL. Significant association existed between elevated serum sPD-L1 levels and menarche age, ethnicity, birth control usage, comorbidity and HER2 status (p<0.05). Menarche age and birth control were identified as independent variables impacting sPD-L1 level by multivariate analysis. However, the OS for patients with high vs low sPD-L1 level was not significant (266.3 months (SD 9.3 months) vs 60.0 months (SD 3.3 months), p=0.647, log-rank test). Additionally, there was no discernible correlation between tissue PD-L1 and serum sPD-L1 levels (p= 0.275, U-test). Elevated blood levels of sPD-L1 were strongly related with a number of clinical traits, and this relationship justifies the need for additional research for diagnostic and prognostic of breast cancer patients.